The Influence of Customer Relationship Strategy, Innovation Strategy and Capability Strategy on Competitive Advantage and Its Implications on Marketing Performance in Small and Medium Enterprises in the City of Bekasi - Winarso, Widi; Limakrisna, Nandan; Muharam, Hari (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Indonesia's position in global competitiveness is considered low compared to other ASEAN countries. This indicates that the competitive advantage of the industry and other SME sectors is considered not optimal. The competition for SMEs in the fashion sector to compete for the market and the increasing number of SMEs has caused the SMEs in the fashion sector to determine the right strategy in marketing their business products. The purpose of this study was to analyze the effect of Customer Relationship Strategy, business innovation strategy and capability strategy on competitive advantage and the performance of SMEs in Bekasi City. This research approach is a quantitative approach. Exogenous variables include Customer Relationship Strategy, innovation and capability strategy. Endogenous variables are competitive advantage and competitive advantage. The endogenous variable in this study is marketing performance. The population of this research is the owners and employees of SMEs in Bekasi City, totaling 561 SMEs. Based on calculations with the Slovin formula, the total sample is 235 SMEs. The analytical method used is the Structural Equation Model (SEM). SEM assumption test consists of outliers, multicollinearity, minimum number of samples. Hypothesis testing using CR and t test.